2007
DOI: 10.4269/ajtmh.2007.77.1051
|View full text |Cite
|
Sign up to set email alerts
|

Human Asymptomatic Infection in Visceral Leishmaniasis: A Seroprevalence Study in an Urban Area of Low Endemicity. Preliminary Results

Abstract: Many aspects of the human asymptomatic visceral leishmaniasis (VL) remain not elucidated, and moreover, almost all the data come from highly endemic areas. The recent appearance of American VL (AVL) in the northeastern region of the state of São Paulo, Brazil, offered a good opportunity for further understanding. We present the preliminary results from a seroprevalence study on AVL in humans in Araçatuba, São Paulo. This was a cross-sectional survey on a random sample of the population (one-stage simple random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 15 publications
6
18
0
Order By: Relevance
“…Because our study included all age groups this feature could be an explanation for the high prevalence reported here. Other studies reported similar L. chagasi infection frequencies in regions with both high and low VL endemicities (Barão et al 2007, Romero et al 2009). …”
Section: Discussionsupporting
confidence: 49%
“…Because our study included all age groups this feature could be an explanation for the high prevalence reported here. Other studies reported similar L. chagasi infection frequencies in regions with both high and low VL endemicities (Barão et al 2007, Romero et al 2009). …”
Section: Discussionsupporting
confidence: 49%
“…Canine visceral leishmaniasis generally precedes human disease in these new areas 4 . This was demonstrated in the visceral leishmaniasis epidemic in Araçatuba, São Paulo State 12,13 . Studies in the State of Rio Grande do Norte show a 32.6% Leishmania infection rate in dogs in an endemic area on the outskirts of the State capital Natal, with a 30% six-month seroconversion rate in these animals.…”
mentioning
confidence: 99%
“…17,18 In areas where VL transmission is anthroponotic, asymptomatic persons might play a role as reservoirs, and even in areas where VL is zoonotic it is speculated that these persons could also contribute to transmission. 7,19 Thus, assessment of the prevalence and distribution of asymptomatic cases would contribute to a better understanding of VL transmission and help in developing control efforts.…”
Section: Introductionmentioning
confidence: 99%